PENGARUH PENGHINDARAN PAJAK, RASIO KEUANGAN, DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Ngui, Cindy Oktavia; Zubaidi, Umar Issa (E-Jurnal Akuntansi TSM, 2025)
This study aims to analyze the factors influencing firm value. These factors include tax avoidance, return on assets, current ratio, debt to equity ratio, dividend policy, firm size, dan sales growth. The research focuses on manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Using a purposive sampling technique, 51 companies met the criteria, resulting in 153 data points. The research model employs multiple linear regression analysis, processed data using SPSS version 25. The findings of this study indicate that return on asset, current ratio, debt to equity ratio and sales growth significant affect on firm value. meanwhile, other independent variables such as tax avoidance, dividend policy, and firm size not have a significant effect on firm value.